Seismicity and structural safety in buildings: lessons learned in Mexico - Juan José Pérez-Gavilán; Jorge Aguirre; Leonardo Ramírez (Instituto Nacional de Salud Pública, 2018)
Motivated by the recent seismic events in México, the seismic environment of the country is reviewed together with the mechanisms and the regions that generate earthquakes. Some of the parameters used to determine the intensity as a difference with the magnitude of earthquakes and the way to make predictions with data coming for seismological stations using attenuation functions are mentioned. It is shown how the structures that collapse after the September 19th, 2017 earthquake in México City are aligned with the transition zone between the old lake region of the Mexican valley and the hill zone. The basic criteria for structural design and how the constructions codes establish the performance level of the structures subjected to actions of different frequency and intensity, are presented. An example is given regarding the relationship that exists between strength, damage and structural performance. Some of the observed damages are presented with ideas regarding some of the aspects that can be improved that have an influence in construction safety.